Effect of an edible nanomultilayer coating by electrostatic self-assembly on the shelf life of fresh-cut mangoes - Souza, Marthyna P. (2015)
This work aims at evaluating the effect of an alginate-chitosan nanomultilayer coating, obtained by electrostatic layer-by-layer self-assembling, in the quality and shelf life of fresh-cut mangoes. Coated and uncoated fresh-cut mangoes were stored under refrigeration (8 °C) for 14 days. The changes in mass loss, titratable acidity, pH, ascorbic acid content, total soluble solids, malondialdehyde content, browning rate, and microbial count were evaluated during storage. At the end of the storage period, lower values of mass loss, pH, malondialdehyde content, browning rate, soluble solids, microorganisms proliferation, and higher titratable acidity were observed in the coated mangoes. The nanomultilayer coating did not improve the retention of vitamin C during storage of fresh-cut mangoes. Results suggest that chitosan-alginate nanomultilayer edible coating extends the shelf life of fresh-cut mangoes up to 8 days.